A Critical Review on the Book An Introduction to Islamic Archaeology - Mohsen Saadati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
From among the topics related to archaeology, archaeologists and researchers have always been interested in the archaeology of the Islamic era, as one the most diverse periods with currents regarding art, architecture, urbanism, etc. The present article intends to describe and review An Introduction to Islamic Archaeology by Marcus Milwright. This research aimed at archaeologically reviewing the Islamic era as one of the important areas in archaeology. The above-mentioned book introduces the Islamic period looking at the social and religious status, some monuments of the Islamic era, cultures, as well as customs and traditions. The current article seeks to review this work in terms of form and content. In such a review, the book is considered in three aspects: technically, structurally, and in terms of writing features. Then in the content review, the accuracy and validity of the material as well as the author’s deficiencies are addressed. The detailed review of this book indicates that despite its remarkable print quality and the relative fluency of the text, the book has several problems in some chapters. In terms of content, the book suffers from a number of drawbacks, for example, it fails to refer to first-hand sources, the images have no reference, there is no general structure for dynasties and governments of the Islamic period and finally, the contents are dispersed given the extensive scope of the subject matter.